Euscelus species of the West Indies (Coleoptera: Attelabidae) - Hamilton, Robert W. (Zootaxa, 2007)
Fourteen species of Euscelus Schoenherr are recognized from the West Indies: E. armatus (Gyllenhal), E. scutellatus (Klug), E. dentipes (Fabricius), E. angulosus (Gyllenhal), E. scrobiculatus Voss, E. uviferae Marshall, E. pulchellus (Suffrian), E. cribrarius (Olivier), E. biguttatus (Fabricius), E. sexmaculatus (Chevrolat), E. aureolus (Gyllenhal), E. haitensis new species from Haiti, E. postoculidens new species and E. dominicanus new species from the Dominican Republic. Four previously described eusceline species from the West Indies are relegated to synonymy: Euscelus cancellatus Voss, new synonymy; Euscelus callosipennis Voss, new synonymy; Euscelus coccolobae (Wolcott), new synon- ymy and Emphyleuscelus cubensis Janczyk, new synonymy. Specimens were unavailable for Attelabus canaliculatus Olivier, Attelabus spinifex Olivier and Attelabus fornicatus Olivier and they are not included. Lectotypes are designated for E. uviferae and E. pulchellus. A key separating West Indian euscelines is provided and the species are covered in standard taxonomic fashion including habitus images and aedeagal illustrations.KEY WORDS: Attelabidae, Leaf rollers, Euscelus, West Indies